2003
DOI: 10.1182/blood-2002-10-3076
|View full text |Cite
|
Sign up to set email alerts
|

Glycophorin C is the receptor for the Plasmodium falciparum erythrocyte binding ligand PfEBP-2 (baebl)

Abstract: We report in this paper that glycophorin C (GPC) is the receptor for PfEBP-2 (baebl, EBA-140), the newly identified erythrocyte binding ligand of Plasmodium falciparum. PfEBP-2 is a member of the Duffy bindinglike erythrocyte binding protein (DBL-EBP) family. Although several reports have been published characterizing PfEBP-2, the identity of its erythrocytic receptor was still unknown. Using a combination of enzymatically treated red blood cells (RBCs) and rare, variant RBCs lacking different surface proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
145
1
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 26 publications
2
145
1
6
Order By: Relevance
“…Contrary to our results, Lobo et al (10) concluded that glycophorin C was the ligand for BAEBL variant (INKK) based on the observation that INKK did not bind to Leach erythrocytes that lack glycophorin C or to Yus erythrocytes that have a deletion of exon 2 of glycophorin C. It was also observed in the previous study that antibodies to glycophorin C partially inhibited the binding of INKK to erythrocytes (10). However, these results are not entirely conclusive because binding to Leach and Yus erythrocytes was performed with erythrocytes frozen as pellets in liquid nitrogen that may have been unsuitable for the binding assay.…”
Section: Binding Of Baebl (Vstk) To Erythrocytes Is Inhibited By Glyccontrasting
confidence: 56%
“…Contrary to our results, Lobo et al (10) concluded that glycophorin C was the ligand for BAEBL variant (INKK) based on the observation that INKK did not bind to Leach erythrocytes that lack glycophorin C or to Yus erythrocytes that have a deletion of exon 2 of glycophorin C. It was also observed in the previous study that antibodies to glycophorin C partially inhibited the binding of INKK to erythrocytes (10). However, these results are not entirely conclusive because binding to Leach and Yus erythrocytes was performed with erythrocytes frozen as pellets in liquid nitrogen that may have been unsuitable for the binding assay.…”
Section: Binding Of Baebl (Vstk) To Erythrocytes Is Inhibited By Glyccontrasting
confidence: 56%
“…The receptor for one of the BAEBL variants is glycophorin C͞D, based on its inability to bind Gerbich-negative (15,16) and glycophorin C͞D-negative erythrocytes (17). On human erythrocytes carrying the Gerbich-negative blood group antigen, glycophorin C is missing part of its peptide backbone.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that distinct isolates of P. falciparum have varying abilities to use alternative invasion pathways, although many of the erythrocyte receptors are yet to be defined (9-13). On the erythrocyte side, several invasion pathways have been described involving the erythrocyte glycophorins, glycophorin A, and glycophorin C͞D, receptor X, receptor Y, and, potentially, glycolipids (8,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmodium falciparum has a sophisticated invasion machinery with several EBL proteins that each bind a different erythrocyte receptor in a sialic acid-dependent manner (1). Erythrocyte-binding antigen 175 (PfEBA-175), erythrocyte-binding ligand 1 (PfEBL-1), and erythrocyte-binding antigen 140 (PfEBA-140) bind glycophorins A, B, and C, respectively (2)(3)(4). A fourth member of this family, erythrocyte-binding antigen 181 (PfEBA-181), binds an unknown receptor (5).…”
mentioning
confidence: 99%